PENGARUH MODEL PEMBELAJARAN QUANTUM TEACHING TERHADAP PEMAHAMAN KONSEP - Jusman Jusman; Rafiqah Rafiqah; St. Hasniwiyah Jawil; Hajeriati Hajeriati (Pendidikan Fisika UIN Alauddin Makassar, 2022)
The research aims to find out the differences in increasing conceptual understanding. students who are taught and not taught use the quantum teaching model assisted by a video-based contextual laboratory. The type of research used is a quasi-experimental research, using Matching pretest-posttest control group design. The results showed that the Quantum Teaching learning model using the Video Based Contextual Laboratory had an effect on the understanding of physics concepts for students.